2004
DOI: 10.1002/chin.200434268
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis in Ionic Liquids

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 1 publication
1
24
0
Order By: Relevance
“…Interest in ILs stems from their potential application as ''green solvents'' (Sheldon et al, 2002). Specifically, due to their high thermal stability and nearly complete non-volatility, ILs are becoming attractive alternatives to volatile and unstable organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in ILs stems from their potential application as ''green solvents'' (Sheldon et al, 2002). Specifically, due to their high thermal stability and nearly complete non-volatility, ILs are becoming attractive alternatives to volatile and unstable organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic efficiencies of the different anions were in the following order: [12,21]. Anions having lower hydrogen bond basicity and nucleophilicity are found to be enzyme-compatible, because low hydrogen bond basicity and nucleophilicity minimize their interference with the internal hydrogen bonds and interaction with the positively charged sites in the enzyme and hence reduce the tendency to change the conformation of the enzyme's structure [12,[21][22][23] …”
Section: Effects Of Ilsmentioning
confidence: 99%
“…The hydrogen bond basicity and nucleophilicity of anions have been found to affect the enzyme activity and stability in IL-based solvent media [12,21]. Anions having lower hydrogen bond basicity and nucleophilicity are found to be enzyme-compatible, because low hydrogen bond basicity and nucleophilicity minimize their interference with the internal hydrogen bonds and interaction with the positively charged sites in the enzyme and hence reduce the tendency to change the conformation of the enzyme's structure [12,[21][22][23]. This difference in (S)-ibuprofen yields could be attributed to the fact that ILs containing [NO 3 6 ]´anions.…”
Section: Effects Of Ilsmentioning
confidence: 99%
“…As detailed in Figure 3, much work has been done throughout this decade with enzymes in ionic liquid media. Excellent review articles have been published during these years collecting the results produced (Kragl et al, 2002;Sheldon et al, 2002Sheldon et al, , 2003Park & Kazlauskas, 2003;Zhao, 2005;van Rantwijk & Sheldon, 2007;Yang, 2009;Moniruzzaman et al, 2010b;Lozano, 2010). Nevertheless, it is important to highlight that most of these results refer to lipase biocatalysis: lipases provide fast and convenient enantioselective synthetic routes for esterification and transesterification reactions.…”
Section: Enzymes In Ionic Liquidsmentioning
confidence: 99%
“…These types of enzymes have received less attention in the literature, and this chapter will focus on the research work performed with laccase and peroxidase biocatalysis using ionic liquid as reaction media. Most biocatalysis in ionic liquids involved no or low water content (Sheldon et al, 2002). Pugin et al (2004) reported the interest in reaction systems with an ionic liquid and water (wet ionic liquids) due to the enantioselectivity of the biocatalyst and the importance in the use with ionic liquids when compared with organic solvents.…”
Section: Enzymes In Ionic Liquidsmentioning
confidence: 99%